Association between visible malocclusion and adolescents’ satisfaction with their dental appearance and function - Virtanen, Terhi (My University, 2020)
Objective. The aim of this study was to analyze the association between visible malocclusion and adolescents’ satisfaction with their dental appearance and function. Materials and methods. The material consisted of a random sample of 1041 adolescents, 388 males and 653 females, with a mean age of 16.3 years. The adolescents were categorized into a case group showing visible malocclusions (n=160) and a control group (n= 881).Subjective data were gathered using a semi-structured questionnaire. Two orthodontists clinically assessed participants’ dental appearance using the Aesthetic Component (AC) of the Index of Orthodontic Treatment Need (IOTN). The adolescents themselves rated their dental appearance on a modified visual analogue scale (VAS). Results. Of all adolescents, over 80% were satisfied with their occlusal function. Instead, adolescents in the case group were less satisfied with the position of their upper incisors than the controls. In the case group, protruding upper incisors were reported as the most important reason for dissatisfaction (13.7%, n=22), followed by crowded or rotated lower incisors (8.1%, n=13) and diastema between upper incisors (7.5%, n=12). In the control group, the most important reasons for dissatisfaction were crowded or rotated lower incisors (6.8%, n=60) and diastema between upper incisors (4.4%, n=39). Increased overjet and congenitally missing incisors were most likely to be aesthetically disturbing, while anterior open bite was most often associated with functional problems. Conclusions: Adolescents with visible malocclusion are more often dissatisfied with their dental appearance and more frequently express self-perceived orthodontic treatment need, compared to control adolescents.
Keywords: Aesthetic Component of the IOTN, occlusal traits, self-perception